2014
DOI: 10.1021/nn505744r
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lithium-Ion Distributions in Nanostructured Block Polymer Electrolyte Thin Films by X-ray Photoelectron Spectroscopy Depth Profiling

Abstract: X-ray photoelectron spectroscopy (XPS) depth profiling with C60(+) sputtering was used to resolve the lithium-ion distribution in the nanometer-scale domain structures of block polymer electrolyte thin films. The electrolytes of interest are mixtures of lithium trifluoromethanesulfonate and lamellar-forming polystyrene-poly(oligo(oxyethylene)methacrylate) (PS-POEM) copolymer. XPS depth profiling results showed that the lithium-ion concentration was directly correlated with the POEM concentration. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 37 publications
8
96
0
Order By: Relevance
“…5,11,12 In such systems, lithium salts have been shown to partition exclusively to the PEO domain. 13,14 Wang and co-workers have suggested that this selective partitioning is primarily due to the large solvation energy gained when the lithium salts complex and associate with the polar PEO domains, leading to a large increase in the effective segregation strength with lithium salt loading. 15,16 Experimental studies have taken advantage of this intriguing behavior to readily and dramatically tune the segregation strength of PS−PEO block copolymers through the addition of a lithium salt, and these studies have shown that a wide range of morphologies can be accessed without the need to modulate temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5,11,12 In such systems, lithium salts have been shown to partition exclusively to the PEO domain. 13,14 Wang and co-workers have suggested that this selective partitioning is primarily due to the large solvation energy gained when the lithium salts complex and associate with the polar PEO domains, leading to a large increase in the effective segregation strength with lithium salt loading. 15,16 Experimental studies have taken advantage of this intriguing behavior to readily and dramatically tune the segregation strength of PS−PEO block copolymers through the addition of a lithium salt, and these studies have shown that a wide range of morphologies can be accessed without the need to modulate temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rigaku Globalfit software was used to fit the XRR profile with repeating lamellae models. The XRR profiles facilitated determination of the polymer densities and interfacial roughnesses through fitting of the oscillation amplitudes, while the layer thicknesses were evaluated by fitting the oscillation periods . The XRR fitting herein used a multiresponse nonlinear regression approach .…”
Section: Methodsmentioning
confidence: 99%
“…Multilayers are frequently used to disclose the depth dependence of the depth resolution . If the distance of the single layers is large enough (and Δ z is small enough) to ensure that the profiles of layers of A are separated by layers of B and do not overlap, the layers of A can be treated like single layers, and Eqn applies (see Fig.…”
Section: Symmetric (Gaussian) Drfmentioning
confidence: 99%
“…In contrast to the UDS model, the MRI model correctly predicts the shift of the measured interface or delta layer profile with respect to the original layer location, and it has been successfully applied to SIMS, AES and XPS depth profiles. The MRI‐DRF can be presented either as an analytical or as a numerical solution both for delta layers and single (thicker) layers.…”
Section: Asymmetric Non‐gaussian Drf For Interfaces and Delta Layersmentioning
confidence: 99%
See 1 more Smart Citation